A case–control study of placental lesions associated with pre‐eclampsia. Issue 2 (28th November 2012) - Devisme, Louise; Merlot, Benjamin; Ego, Anne; Houfflin‐Debarge, Veronique; Deruelle, Philippe; Subtil, Damien
Abstract: Objective: To investigate gross and microscopic placental lesions associated with pre‐eclampsia and to determine which lesions are most strongly linked to serious pregnancy complications. Methods: A retrospective case–control study of 173 placentas from women with pre‐eclampsia and 173 placentas from healthy normotensive women was conducted. Results: The mean placental weight in the pre‐eclampsia group was lower than that recorded for the control group (280 g vs 360 g; P < 0.001). Infarcts (65.9% vs 13.2%; P < 0.001) and placental abruption ( P < 0.001) were most frequent among women with pre‐eclampsia. Microscopic findings showed the following lesions to be associated with pre‐eclampsia: hypermature villi, defined by absence of intermediate villi (72% vs 16%; P < 0.001), excessive syncytial knots (90% vs 9%; P < 0.001), decidual vasculopathy (51% vs 8%; P < 0.001), villous fibrosis (6% vs 0%; P < 0.001), erythroblastosis (11% vs 4%; P < 0.01), and avascular terminal villi (9% vs 3%; P < 0.05). Increased syncytial knots, infarcts, basal decidual vasculopathy, hypermature villi, and placental erythroblastosis were still associated with pre‐eclampsia after logistic regression modeling. Conclusion: Placental lesions most strongly associated with pre‐eclampsia were all causes or expressions of placental hypoxia or ischemia, which appears as the primary mechanism of pre‐eclampsia.